2017
DOI: 10.12669/pjms.334.11696
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of 3105 Medico Legal Cases at Tertiary Care Hospital, Rawalpindi

Abstract: Background and Objectives:Medico legal cases are essential component of medical practice and comprise most important constituent of emergencies. The reporting of such cases is imperative to recognize theirsocioeconomic burden on any country. The present study was conducted to scrutinize different categories of medico legal cases and characteristics of the victims at casualty department oftertiary care hospital Rawalpindi. The objective of the study was to find out the frequency ofvarious categories of medico l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
2
11
2
3
Order By: Relevance
“…Uno de los resultados más interesantes de nuestro registro es la baja proporción de traumas cerrados de abdomen que observamos (33%), lo que contrasta con los datos de reportes europeos (87-90%) 11,12 , asiáticos (64-95%) [23][24][25] , australianos (75-83%) 13 y norteamericanos 14 , en los que los accidentes de tráfico y las caídas representan la principal causa de trauma abdominal. En contraste, reportamos una alta proporción de traumas penetrantes de abdomen (67%), que se corresponde con las realidades de otros países como Brasil (69-78%) 16,17 globalmente 13,20 , estas diferencias se explican más por las condiciones sociales, económicas y de violencia de países como México y Brasil, además del escaso control sobre el acceso a armas de fuego en la población civil 2,5,6,19 .…”
Section: Discussionunclassified
“…Uno de los resultados más interesantes de nuestro registro es la baja proporción de traumas cerrados de abdomen que observamos (33%), lo que contrasta con los datos de reportes europeos (87-90%) 11,12 , asiáticos (64-95%) [23][24][25] , australianos (75-83%) 13 y norteamericanos 14 , en los que los accidentes de tráfico y las caídas representan la principal causa de trauma abdominal. En contraste, reportamos una alta proporción de traumas penetrantes de abdomen (67%), que se corresponde con las realidades de otros países como Brasil (69-78%) 16,17 globalmente 13,20 , estas diferencias se explican más por las condiciones sociales, económicas y de violencia de países como México y Brasil, además del escaso control sobre el acceso a armas de fuego en la población civil 2,5,6,19 .…”
Section: Discussionunclassified
“…11 Urban areas have higher traffic accident rates than rural areas. Malik et al 12 found traffic accidents as one of the highest contributors to injury rates with 25% of cases occurring in rural areas and 74% in urban areas. Subjects who work have a higher risk of having accidents while working and accidents while travelling to and from work.…”
Section: Figure 3 Cases Of Natural and Unnatural Deaths Per Yearmentioning
confidence: 99%
“…Romana Malik et al depict in their study that cause of death are 40 % RTA (Road Traffic Accident), 31% blunt injury, 19% sharp injury, 2% sexual assault, 4% poisoning and 4% firearm cases. 14 Study conducted in Ethopia by Solano showed the cause of deaths in forensic science are due to strangulation (7.5%), suffocation (0.8%) others (0.5%), hanging (88%), poisoning (10%), bullet(0.7%), drowning (8.5%), electric current injury, burn (0.8%). 15 This report is comparatively different from the reports of the current study as cause of death by Blunt injury cases were higher in number which is immediately followed by hanging and then other causes.…”
Section: Cause Of Death Wise Analysismentioning
confidence: 99%